2021
DOI: 10.1001/jamanetworkopen.2021.0694
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cannabis Retailer Proximity and Density With Cannabis Use Among Pregnant Women in Northern California After Legalization of Cannabis for Recreational Use

Abstract: Open Access. This is an open access article distributed under the terms of the CC-BY License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 5 publications
2
17
0
Order By: Relevance
“…Cannabis-attributable ED visits increased starting in May 2020, coinciding with large increases in per-capita stores and cannabis sales. This finding is consistent with evidence suggesting that commercialization of recreational cannabis, including greater retail availability of cannabis stores, is associated with higher rates of cannabis use and harms in a variety of populations in the United States [17,[23][24][25]. The reported changes in cannabis-attributable ED visits align with survey data from Ontario, which show that the percentage of Ontarians reporting daily or almost daily cannabis use did not change significantly between pre-legalization (4.9%, 95% CI = 3.3, 6.6 in Q1, 2018) and the first year postlegalization (6.0%, 95% CI = 5.1, 7.1 in Q1-4, 2019) before almost doubling to 9.3% (95% CI = 7.9, 12.1) during the period of market commercialization and COVID-19 (Q4, 2020) [7].…”
Section: Table 1 Describes Observed Changes In Cannabis-attributable Edsupporting
confidence: 88%
“…Cannabis-attributable ED visits increased starting in May 2020, coinciding with large increases in per-capita stores and cannabis sales. This finding is consistent with evidence suggesting that commercialization of recreational cannabis, including greater retail availability of cannabis stores, is associated with higher rates of cannabis use and harms in a variety of populations in the United States [17,[23][24][25]. The reported changes in cannabis-attributable ED visits align with survey data from Ontario, which show that the percentage of Ontarians reporting daily or almost daily cannabis use did not change significantly between pre-legalization (4.9%, 95% CI = 3.3, 6.6 in Q1, 2018) and the first year postlegalization (6.0%, 95% CI = 5.1, 7.1 in Q1-4, 2019) before almost doubling to 9.3% (95% CI = 7.9, 12.1) during the period of market commercialization and COVID-19 (Q4, 2020) [7].…”
Section: Table 1 Describes Observed Changes In Cannabis-attributable Edsupporting
confidence: 88%
“…Data from a nationally representative sample of pregnant women in the United States indicated that the prevalence of self‐reported past‐month cannabis use increased from 3.4% in 2002–2003 to 7.0% in 2016–2017 (Volkow, Han, Compton, & McCance‐Katz, 2019). Importantly, as US states continue to legalize cannabis for recreational use (Geiger, 2016; State Medical Marijuana Laws, 2017), cannabis use among pregnant women may increase even more markedly (Gnofam, Allshouse, Stickrath, & Metz, 2020; Skelton, Hecht, & Benjamin‐Neelon, 2020, 2021; Young‐Wolff et al, 2021). Animal models have indicated that in‐utero exposure to cannabis is associated with cognitive abnormalities and impairments in outcomes that simulate neuropsychiatric impairments in humans (Nashed, Hardy, & Laviolette, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, another study found Dutch individuals who lived closer to a coffee shop were more likely to start cannabis at an earlier age (Palali & vanOurs, 2015). In California, longer drive time to the nearest outlet was associated with lower odds of cannabis use among pregnant women in California, OR = 0.96; 95% CI = 0.95–0.98 (Young‐Wolff et al., 2021). Having more retailers within a 15‐min drive was also associated with an increased likelihood of cannabis consumption (Young‐Wolff et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In California, longer drive time to the nearest outlet was associated with lower odds of cannabis use among pregnant women in California, OR = 0.96; 95% CI = 0.95–0.98 (Young‐Wolff et al., 2021). Having more retailers within a 15‐min drive was also associated with an increased likelihood of cannabis consumption (Young‐Wolff et al., 2021). Washington State residents who lived close to a cannabis retailer were more likely to report current use or frequent use (Everson et al., 2019).…”
Section: Introductionmentioning
confidence: 99%